2018
DOI: 10.1007/s10548-018-0689-9
|View full text |Cite
|
Sign up to set email alerts
|

Transient Topographical Dynamics of the Electroencephalogram Predict Brain Connectivity and Behavioural Responsiveness During Drowsiness

Abstract: As we fall sleep, our brain traverses a series of gradual changes at physiological, behavioural and cognitive levels, which are not yet fully understood. The loss of responsiveness is a critical event in the transition from wakefulness to sleep. Here we seek to understand the electrophysiological signatures that reflect the loss of capacity to respond to external stimuli during drowsiness using two complementary methods: spectral connectivity and EEG microstates. Furthermore, we integrate these two methods for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 93 publications
(155 reference statements)
8
22
0
Order By: Relevance
“…Chennu et al highlighted that the re-emergence of behavioral awareness is correlated with the fronto-parietal alpha band wPLI connectivity. In addition, other studies showed that a decrease in the posterior-anterior alpha band's wPLI connectivity was associated with the transition into unconsciousness due to sedation or sleep [29][30][31]. Based on these previous results, and considering our findings showing that wPLI connectivity in the alpha band was decreased in the sham and increased in the active sessions (which led to a significant increase in fronto-parietal alpha band connectivity), we may argue that anodal tDCS deprived patients of drowsiness in the active session.…”
Section: Discussionmentioning
confidence: 99%
“…Chennu et al highlighted that the re-emergence of behavioral awareness is correlated with the fronto-parietal alpha band wPLI connectivity. In addition, other studies showed that a decrease in the posterior-anterior alpha band's wPLI connectivity was associated with the transition into unconsciousness due to sedation or sleep [29][30][31]. Based on these previous results, and considering our findings showing that wPLI connectivity in the alpha band was decreased in the sham and increased in the active sessions (which led to a significant increase in fronto-parietal alpha band connectivity), we may argue that anodal tDCS deprived patients of drowsiness in the active session.…”
Section: Discussionmentioning
confidence: 99%
“…However, our participant was awake during the whole session, and the EEG data show no sleeprelated signs. Latest findings from research in REM sleep and ketamine anesthesia suggest that a decrease in alpha power may be a marker for a disconnection of consciousness from sensory stimuli (Sanders et al, 2012;Darracq et al, 2018;Comsa et al, 2019). Increases in theta power have been found to be associated with cognitive control and stable attention (Cavanagh and Frank, 2014;Keller et al, 2017) as well as with decreased activity in the DMN (White et al, 2013;Hacker et al, 2017), which is related to self-processing and mind-wandering.…”
Section: Discussionmentioning
confidence: 99%
“…Here we suggest one powerful novel route that takes advantage of the recent trend towards big data to explore subtle fluctuations in conscious level during normal wakefulness, modulated by alertness, task and performance. [14][15][16][17] In this way we are effectively combining the above two consciousness science paradigms, bridging between level-and content-centred approaches to consciousness, in a way that may yield important novel insights into the components of consciousness. 14 We here focus on the Cambridge Centre for Ageing and Neuroscience (CamCAN) database, 18 a large multimodal dataset which includes RS and task-based functional magnetic resonance imaging (fMRI), magnetoencelography (MEG) and behavioural data on a large cohort of healthy subjects across the adult lifespan.…”
Section: Introductionmentioning
confidence: 99%